HUBUNGAN ANTARA INTENSITAS MENGAJI AL-QUR’AN DI PANTI ASUHAN AL-JAMI’YATUL WASHLIYAH DENGAN KEMAMPUAN MEBACA TEKS ARAB SISWA MADRASAH TSANAWIYAH AL-WASHLIYAH MEDAN - Ahsani Madina; Muhammad Taufiq (Yayasan Haiah Nusratul Islam, 2026)
Reciting the Qur'an is a mandatory activity for students residing at Al-Jam'iyatul Washliyah Orphanage, Brayan Medan. Qur'an recitation has become a daily routine involving the repeated reading of Arabic letters, words, and verses, which may enhance students' ability to recognize and read Arabic texts while reciting the Qur'an. However, the influence of the intensity of Qur'an recitation on Arabic text reading ability still requires empirical evidence. This study aims to describe the intensity of Qur'an recitation and students' Arabic text reading ability, as well as to analyze the influence of the intensity of Qur'an recitation on Arabic text reading ability. This study employed a quantitative method using a simple linear regression approach. The population consisted of 50 students, with a sample of 30 students selected through purposive sampling. Data were collected using a questionnaire and an Arabic text reading test, both of which had been tested for validity and reliability. The data were analyzed using normality, linearity, and simple linear regression tests. The findings revealed that the intensity of Qur'an recitation had a significant influence on students' Arabic text reading ability (Sig. = 0.000 < 0.05). The coefficient of determination (R²) was 0.565, indicating that the intensity of Qur'an recitation contributed 56.5% to students' Arabic text reading ability.